Estimation of Helmert Orthometric Heights Using Digital Barcode Levelling, Observed Gravity and Topographic Mass-Density Data Over Part of the Darling Scarp, Western Australia - Featherstone, Will; Allister, N. (Institution of Surveyors, Australia, 2001)
The normal orthometric corrections used in the 1971 establishment of the Australian Height Datum (AHD) do not properly account for local variations in the Earth?s gravity field. Therefore, Helmert orthometric heights have been computed over a spirit-levelled height traverse over part of the Darling Fault and compared with normal orthometric heights. This involves a measured height change of ~175m, a measured gravity change of ~34mGal, and an estimated change in topographic mass-density of 480kgm-3. The computed Helmert orthometric correction reaches -4.8mm between the end-points of the traverse, whereas the normal orthometric correction only reaches 0.1mm. However, computing the corrections over each bay in the traverse gives totals over the entire traverse of -0.8 mm for the Helmert orthometric corrections and 0.2 mm for the normal orthometric corrections. A difference of 0.1 mm was observed between the Helmert orthometric corrections computed with constant and variable topographic mass-density models. It is recommended that orthometric corrections, which take into account observed gravity and topographic mass-density, be considered in any future redefinition of the AHD.